Bacteria and Bellicosity: Photoperiodic Shifts in Gut Microbiota Drive Seasonal Aggressive Behavior in Male Siberian Hamsters. Issue 3 (June 2022) - Shor, Elyan K.; Brown, Shawn P.; Freeman, David A.
The existence of a microbiome-gut-brain axis has been established wherein gut microbiota significantly impacts host behavior and physiology, with increasing evidence suggesting a role for the gut microbiota in maintaining host homeostasis. Communication between the gut microbiota and the host is bidirectional, and shifts in the composition of the gut microbiota are dependent on both internal and external cues (host-derived signals, such as stress and immunity, and endocrine and environmental signals, such as photoperiod). Although there is host-driven seasonal variation in the composition of the microbiota, the mechanisms linking photoperiod, gut microbiota, and host behavior have not been characterized. The results of the present study suggest that seasonal changes in the gut microbiota drive seasonal changes in aggression. Implanting short-day Siberian hamsters ( Phodopus sungorus ) with fecal microbiota from long-day hamsters resulted in a reversal of seasonal aggression, whereby short-day hamsters displayed aggression levels typical of long-day hamsters. In addition, there are correlations between aggressive behavior and several bacterial taxa. These results implicate the gut microbiota as part of the photoperiodic mechanism regulating seasonal host behavior and contribute toward a more comprehensive understanding of the relationships between the microbiota, host, and environment.